Double Vulnerabilities of Unregistered Wife After The New Kuhp: An Analysis of The Cohabitation Article As a Threat of Structural Victimization - Rizky Wibowo; Nahar Surur (Socio Legal and Islamic Law, 2025)
Article 412 of Law No. 1 of 2023 concerning the Criminal Code (the Cohabitation Article) is often promoted as a guardian of public morality. However, for those practicing nikah siri (unregistered marriage), this article creates a new dimension of threat that did not previously exist. This study aims to dissect how the cohabitation article in the New Criminal Code potentially serves as an instrument of structural victimization for unregistered wives. This study employs a socio-legal research method with a criminological-victimology and critical legal theory approach. The study finds that unregistered wives face "double vulnerability." First, civil vulnerability due to the lack of legal protection regarding alimony, inheritance, and child status due to the absence of official records. Second, criminal vulnerability where they are now at risk of being reported for cohabitation offenses by third parties (family/relatives) or being criminalized by their own unregistered husbands as a tool of intimidation in domestic disputes. This article challenges the government's narrative that complaint-based offenses (delik aduan) are "safe." The research proves that instead of protecting the institution of the family, this article facilitates structural victimization against women by strengthening the husband's bargaining power in unequal unregistered relationships, thereby positioning the state not as a protector, but as an actor that exacerbates domestic oppression